2015
DOI: 10.1080/23311916.2014.993157
|View full text |Cite
|
Sign up to set email alerts
|

Multi-constrained optimization in ball-end machining of carbon fiber-reinforced epoxy composites by PSO

Abstract: This paper presents an approach for the determination of the optimal machining parameters (spindle speed, feed rate and depth of cut) in ball-end milling process of carbon fiber-reinforced plastics (CFRP). In this case, considering the machining force and surface roughness as the constrains, maximum material removal rate is created through coupling response surface method (RSM) and particle swarm optimization (PSO). Many experiments on CFRP were conducted to obtain machining force and surface Roughness values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…The TiAlN coating increased the nose radius, reduced the sharpness of the cutting edge and led to an increase in the height deviation. This is consistent with some studies [ 29 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The TiAlN coating increased the nose radius, reduced the sharpness of the cutting edge and led to an increase in the height deviation. This is consistent with some studies [ 29 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…It was observed that the feed was the most influential factor. This result is in agreement with the literature, where Shahrajabian and Farahnakian [ 29 ] reached similar conclusions. They studied the effect of the feed and tool diameter on the surface roughness after machining.…”
Section: Discussionsupporting
confidence: 93%
“…For the CFRP, the values of Ra and Rz parameters were influenced by the feed rate and, to a lesser extent, by the S × f z interaction. Similar conclusions have been reported in [30]. The milling strategy did not statistically significantly affect the surface roughness results in any of the analysed cases.…”
Section: Discussionsupporting
confidence: 88%
“…Effects of feed per blade and helix angle on material height differences height differences could be recorded [35,36]. The results were also affected by the tool geometry [18]. A comparison of how the helix angle affected the material height difference values obtained during machining with variable parameters v c and f z shows that in most cases the lowest material height difference values were recorded when using a milling cutter with the highest value of the angle λ s .…”
Section: Resultsmentioning
confidence: 94%
“…They showed that the occurrence of the shape deviations on the surface of the workpiece depends on the cutting forces and the wear of the tool on the orientation of the fiber. In [18] it was found that the surface quality of CFRP composites after machining is influenced by the material and geometry of tool, but not by the radial depth of cut. Liu et al [19] drew a similar conclusion.…”
Section: Introductionmentioning
confidence: 99%